2009
DOI: 10.1002/ajpa.21247
|View full text |Cite
|
Sign up to set email alerts
|

Synanthropic primates in Asia: Potential sentinels for environmental toxins

Abstract: Macaques are similar to humans both physiologically and behaviorally. In South and Southeast Asia they are also synanthropic, ecologically associated with humans. Synanthropy with humans raises the possibility that macaques come into contact with anthropogenic toxicants, such as lead and mercury, and might be appropriate sentinels for human exposures to certain toxic materials. We measured lead (Pb) and mercury (Hg) levels and characterized the stable isotopic compositions of δ 15 N and δ 13 C in hair from thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 40 publications
(35 reference statements)
0
29
4
Order By: Relevance
“…The potential for cross-species transmission exists wherever humans and NHP come into contact. Human-NHP interaction is common in Asia, particularly in Bangladesh, where humans and NHP have lived sympatrically for centuries (6)(7)(8)(9). The contexts of contact between humans and NHP in Bangladesh are a microcosm of what is seen in much of South and Southeast Asia.…”
mentioning
confidence: 99%
“…The potential for cross-species transmission exists wherever humans and NHP come into contact. Human-NHP interaction is common in Asia, particularly in Bangladesh, where humans and NHP have lived sympatrically for centuries (6)(7)(8)(9). The contexts of contact between humans and NHP in Bangladesh are a microcosm of what is seen in much of South and Southeast Asia.…”
mentioning
confidence: 99%
“…Hair was plucked using gloved hands, placed into sterile 15 mL plastic tubes, and stored in a cool, dark place. Research has indicated significant variation in macaque hair growth (Engel et al 2010). Following recent work on lead levels in macaque hair (Engel et al 2010), we assume that an average hair sample represents approximately 100 days of growth (approx.…”
Section: Methodsmentioning
confidence: 99%
“…Research has indicated significant variation in macaque hair growth (Engel et al 2010). Following recent work on lead levels in macaque hair (Engel et al 2010), we assume that an average hair sample represents approximately 100 days of growth (approx. 50 mm of hair with an estimated average growth rate of 0.5 mm per day).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations